Soziologische Fachtexte aus Korpusperspektive. Zum Auffinden indirekter Rede in den Annali di Sociologia/Jahrbüchern für Soziologie - Hornung, Antonie (Linguistik Online, 2009)
This paper deals with the question of which search strategies are adapted to corpus analysis when trying to point out textual phenomena such as, for instance, indirect and direct speech. My study investigates the quantity and the various forms of direct and indirect speech used to make references to others’ research. It draws upon the corpus of the German originals published in the Annali di Sociologia from 1991 to 2002, a journal edited in German and Italian (originals and translations in both languages) by the University of Trento, Italy.